Disinflations and income distribution (2020)
Most countries in the world have brought inflation down to very low rates. While there is broad consensus regarding the fact that polices aimed at bringing down inflation have adverse consequences on aggregate output and unemployment, at least in the short run, we know little about the distributional impact of disinflations. We find that along with disinflation, the income distribution tends to worsen: the Gini increases and the income share of those at the top of the income distribution significantly increases. We discuss the implications of these findings for monetary policy.